Child pornography and sexual grooming: legal and societal responses - Ost, Suzanne (Cambridge studies in law and society, 2009)
Child pornography and sexual grooming provide case study exemplars of problems that society and law have sought to tackle to avoid both actual and potential harm to children. Yet despite the considerable legal, political and societal concern that these critical phenomena attract, they have not, thus far, been subjected to detailed socio-legal and theoretical scrutiny. How do the society and law construct the harms of child pornography and grooming? What impact do construction of the child have upon legal and societal responses to these phenomena? What has been the impetus behind the expanding criminaliziation of behaviour in these areas? Suzanne Ost addresses these and other important questions, exploring the critical tensions within legal and social discourses which must be tackled to discourage moral panic reactions towards child pornography and grooming, and advocating a new, more rational approach toward combating these forms of exploitation. (Quelle: Text Verlagseinband / Verlag)